2016
DOI: 10.1016/j.apcatb.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol hydrogenolysis into useful C3 chemicals

Abstract: Applications of renewable biomass provide facile routes to alleviate the shortage of fossil fuels as well as to reduce the emission of CO 2. Glycerol, which is currently produced as a waste in the biodiesel production, is one of the most attractive biomass resources. In the past decade, the conversion of glycerol into useful chemicals has attracted much attention, and glycerol is mainly converted by steam reforming, hydrogenolysis, oxidation, dehydration, esterification, carboxylation, acetalization, and chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
167
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(177 citation statements)
references
References 177 publications
(227 reference statements)
4
167
0
6
Order By: Relevance
“…Multimetallic Structures . Glycerol hydrogenolysis to 1,3‐PDO attracts wide research interest because it provides an alternative route to biocatalytic conversion of glucose . Although recent work has shown that surface carboxylic intermediates adsorbed on metal surface might influence the position where C−O cleavage rupture occurs, it is still generally accepted that catalyst structures are crucial for both activity and selectivity towards 1,3‐PDO formation during glycerol hydrogenolysis.…”
Section: Figurementioning
confidence: 94%
“…Multimetallic Structures . Glycerol hydrogenolysis to 1,3‐PDO attracts wide research interest because it provides an alternative route to biocatalytic conversion of glucose . Although recent work has shown that surface carboxylic intermediates adsorbed on metal surface might influence the position where C−O cleavage rupture occurs, it is still generally accepted that catalyst structures are crucial for both activity and selectivity towards 1,3‐PDO formation during glycerol hydrogenolysis.…”
Section: Figurementioning
confidence: 94%
“…Hydrogenolysis of glycerol to diols is one of the most important approaches to valorization . The product selectivity is critically dependent on the catalyst composition and structure.…”
Section: Introductionmentioning
confidence: 99%
“…10,25,28 This conversion could be achieved by controlling the hydrogenation of glycerol to propanols. Sun et al.…”
Section: ■ Introductionmentioning
confidence: 99%